2003
DOI: 10.3327/jnst.40.509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dissolved Hydrogen on Structure of Oxide Film on Alloy 600 Formed in Primary Water of Pressurized Water Reactors

Abstract: In order to investigate the relationship between the susceptibility of primary water stress corrosion cracking (PWSCC) in Alloy 600 and the content of dissolved hydrogen (DH) in the primary water of pressurized water reactors (PWR), structural analysis of oxide films formed under four different DH conditions in simulated primary water of PWR was carried out using a grazing incidence X-ray diffractometer (GIXRD), a scanning electron microscope (SEM) and a transmission electron microscope (TEM). In particular, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…This result is consistent with the oxide film formed on the nickel-based alloy under the same condition as the present authors reported previously. 26) The material used in this study was 316SS, which differs from 304SS primarily in that molybdenum is added to the former to reduce corrosion. For this reason, it was thought that molybdenum might play an important role in corrosion resistance by protecting the oxide film.…”
Section: Oxide Film Characterizationmentioning
confidence: 99%
“…This result is consistent with the oxide film formed on the nickel-based alloy under the same condition as the present authors reported previously. 26) The material used in this study was 316SS, which differs from 304SS primarily in that molybdenum is added to the former to reduce corrosion. For this reason, it was thought that molybdenum might play an important role in corrosion resistance by protecting the oxide film.…”
Section: Oxide Film Characterizationmentioning
confidence: 99%
“…Furthermore, cross-sectional images and chemical compositions were observed with a scanning transmission electron microscope using energy dispersive X-ray spectroscopy (STEM-EDS). 19) Some results from X-ray diffraction (XRD), the Rutherford back scattering spectroscope (RBS) and the X-ray photoelectron spectroscope (XPS) were shown previously.…”
Section: Multilateral Surface Analysesmentioning
confidence: 82%
“…19) Then the cross-sections of oxide films were observed by scanning transmission electron microscope (STEM) and energy dispersive X-ray spectroscope (EDS).…”
Section: )mentioning
confidence: 99%
“…[8][9][10][11][12] Typical PWR conditions are 295-325°C, <0.01 ppm O 2 , 2-3 ppm H 2 , 1-40 µS/cm, pH300°C 7-7.4, 0.1-3.5 ppm Li, and 0-2300 ppm H 3 BO 3 . 13 The deposition of CRUD can also occur in the secondary circuit of the PWR, operating at lower temperatures (T < 288°C) and different water chemistry (5 ppm of morpholine, 0.3 ppm, <5 ppb of O 2 , room temperature pH~8.5, conductivity~2 µS/cm). One of the most important examples of CRUD-related issue is the clogging tube support plates.…”
mentioning
confidence: 99%
“…The oxide that forms on stainless steels and nickel based alloys in PWR primary water usually comprises two layers. 13 The inner layer, only a few nanometres thick, consists of a protective Cr-rich layer (identified as NiCr 2 O 4 ) and grows by a solid-state diffusion mechanism. 20 It has been suggested that the inner layer comprises a Cr-oxide sublayer at the metal/oxide interface, which is the main contributor to protection from corrosion.…”
mentioning
confidence: 99%